Toxocara Myopericarditis and Cardiac Magnetic Resonance Imaging in a Young Girl - Addison Gearhart; Timothy J. Savage; Thomas J. Sandora; Gabriella S. Lamb; Andrew J. Powell; Roger E. Breitbart (Case Reports in Pediatrics)
Cardiac infection with Toxocara is rarely diagnosed, especially in children, and corresponding cardiac magnetic resonance imaging (CMR) has not been reported. We present a probable case, a 9-year-old girl with myopericarditis, eosinophilia, positive Toxocara serology, and CMR findings consistent with myocardial edema.